2019
DOI: 10.5114/bta.2019.87578
|View full text |Cite
|
Sign up to set email alerts
|

Towards the production of microalgae biofuels: the effect of the culture medium on lipid deposition

Abstract: Microalgae have been studied in recent years for various reasons, one among them being their potential in the production of biofuels. Biofuels are considered as a renewable source that does not compete with the food industry, and their production results in a reduced environmental footprint. The objective of the present study was to evaluate the different culture conditions that influence the productivity of the microalgae Chlorella vulgaris and Scenedesmus obliquus as a potential source for the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…According to Cuellár-García et al [58,59], the type and concentration of the carbon source are particular to every single strain. Some are adapted to high carbonaceous environments, while others do not tolerate high levels of this ion, which in turn may synthesize more or carbohydrates, lipids, or even proteins.…”
Section: Discussionmentioning
confidence: 99%
“…According to Cuellár-García et al [58,59], the type and concentration of the carbon source are particular to every single strain. Some are adapted to high carbonaceous environments, while others do not tolerate high levels of this ion, which in turn may synthesize more or carbohydrates, lipids, or even proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies reported that few species of microalgae and cyanobacteria possess an inherent capacity for lipid synthesis and storage (Table 1). Initially, the studies focused on applying industrially relevant strains such as Spirulina (Arthorspira) [17], Auxenochlorella [18], Botryococcus [19,20], Chlamydomonas [21][22][23], Chlorella [24][25][26][27][28][29], Dunaliella [34], Scenedesmus [38][39][40][41][42][43], and Tetraselmis [44,45]. Over time, other strain with a unique capacity for the synthesis of lipids and hydrocarbons such as Botryococcus braunii [19,20] were isolated and identified, and more recently, the scientific community has opted for the production of mutant strains with large lipid storage [22,23,31].…”
Section: How the Production Of Algae-based Biofuels Changed Over Timementioning
confidence: 99%
“…Microalgae and cyanobacterium are renowned for their high photosynthetic efficiency and ability to generate different metabolites of interest, such as lipids [9], proteins [10], pigments [11], and carbohydrates [12]. Three key elements are needed to produce this microorganism: (1) a carbon source (usually in the form of CO 2 or inorganic form); (2) a culture medium with a sufficient nutrient concentration; and (3) a source of energy-in this case, light, which is known as photosynthetically active radiation [13,14].…”
Section: Introductionmentioning
confidence: 99%